2014
DOI: 10.4238/2014.april.17.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mycophenolate mofetil on the expression of monocyte chemoattractant protein-1 and fibronectin in high glucose cultured human mesangial cells

Abstract: ABSTRACT. The effects of high glucose on the expression of monocyte chemoattractant protein-1 (MCP-1) and the main component of the extracellular matrix, fibronectin (FN), were explored in human mesangial cells (HMCs), along with the intervention effects of mycophenolate mofetil (MMF) on these indicators. Cultured HMCs were divided into five groups: 1) normal control group (5 mM glucose); 2) high glucose group (30 mM glucose); 3) mannitol osmotic pressure control group (5 mM glucose + 25 mM mannitol); 4) high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…19 Mounting evidence demonstrates that the expression of fibronectin and collagen IV is upregulated in RMCs in response to high glucose conditions. 20 Recently, many studies have demonstrated that inflammation has a central role in the progression of diabetic nephropathy. 21 High glucose upregulates the expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…19 Mounting evidence demonstrates that the expression of fibronectin and collagen IV is upregulated in RMCs in response to high glucose conditions. 20 Recently, many studies have demonstrated that inflammation has a central role in the progression of diabetic nephropathy. 21 High glucose upregulates the expression of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Next, in order to rule out the possibility that the high osmotic pressure in the high-dose glucose solution affected the NET formation, we employed mannitol with osmotic pressure similar to glucose [15]. Since the exposure to 20 m M glucose, but not to mannitol, for 2 h at 37°C induced NETs (fig.…”
Section: Resultsmentioning
confidence: 99%
“…MPA might downregulate the expression of TGF- β and CCN2 by reducing intracellular GTP accumulation via suppressing the activity of IMPDH, deactivating most G protein and blocking intracellular signal pathway [ 63 ]. A recent study also demonstrated that the expression of monocyte chemoattractant protein-1 (MCP-1) as well as the secretion of fibronectin (FN) was inhibited by MMF in human mesangial cells (HMCs) exposed to high glucose [ 64 ]. These results suggested that MMF played the antifibrotic effect on diabetic nephropathy through suppressing CCN2 and FN expression.…”
Section: Other Renoprotective Agents Which Can Nonspecifically Inhmentioning
confidence: 99%